just doing homework

(- 7x^2y + xy + 3x + 2) + (5 x^2y - 5 xy - 6x - 7)

Opening the brackets, we get

= -7x^2y + xy + 3x + 2 + 5x^2y - 5xy - 6x - 7

Separating the like terms , we get

= -7x^2y + 5x^2y + xy - 5xy + 3x - 6x - 7 + 2

= -2x^2y - 4xy - 3x - 5

Hence (- 7x^2y + xy + 3x + 2) + (5 x^2y - 5 xy - 6x - 7) = -2x^2y - 4xy - 3x - 5

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up